Porous Si/C microspheres decorated with stable outer carbon interphase and inner interpenetrated Si@C channels for enhanced lithium storage. (August 2019) - Yi, Zheng; Qian, Yong; Cao, Changhe; Lin, Ning; Qian, Yitai
Abstract: The dual-functional carbons are decorated on porous Si microspheres with interpenetrated Si@C channel and stable outer carbon interphase, which are employed to boost the lithium storage and remedy the vital shortcomings of the Si anode, in terms of unstable solid−electrolyte interphase layer, terrible electronic conductivity, huge volume changes as well as bad cycling or rate capability. In this designed composite, the outer carbon layer can perfectly maintain the structure stability and avoid direct contact of Si with electrolyte during cycling, thus resulting in stable solid−electrolyte interphase film and improved initial coulombic efficiency. Furthermore, the inner carbon layer coated directly onto the porous Si framework can effectively enhance the overall conductivity, let the lithium insert fully and endow the composite with higher capacity in half and full cell. As a result, the as-prepared porous Si/C microspheres deliver a reversible capacity of 1660 mAh g −1  at 0.2 A g −1 after 100 cycles and 826.8 mAh g −1 at 2 A g −1 after 200 cycles. Graphical abstract: Dual-functional carbons are developed to remedy the vital shortcomings of the commercial Si anode, in terms of unstable solid−electrolyte interphase layer, terrible electronic conductivity, huge volume changes as well as bad cycling or rate capability.Image 1